2002
DOI: 10.2116/analsci.18.109
|View full text |Cite
|
Sign up to set email alerts
|

Using Reactands in CMOS-based Calorimetric Sensors: New Functional Materials for Electronic Noses

Abstract: One of the major targets for public health is the safety and quality of products addressed to human consumption which may be characterized by their taste and smell. Electronic noses have been developed in order to yield information on these basic parameters by using solid state gas sensors in combination with conventional polymers for the detection of various analytes. [1][2][3][4][5][6][7][8] However, due to their still insufficient selectivity, current gas sensors do not allow one to detect all single compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Reactands may be used in optical artificial noses [34] but the development of more selective calorimetric and capacitive microsensors for electronic noses is promising as well, because chemical reactions yield changes in both the reaction enthalpy and the dipole moment [ 15]. The covalent immobilisation of reactands on AFM or SNOM sensor surfaces may be beneficial for a selective recognition of functional groups with a high local resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactands may be used in optical artificial noses [34] but the development of more selective calorimetric and capacitive microsensors for electronic noses is promising as well, because chemical reactions yield changes in both the reaction enthalpy and the dipole moment [ 15]. The covalent immobilisation of reactands on AFM or SNOM sensor surfaces may be beneficial for a selective recognition of functional groups with a high local resolution.…”
Section: Discussionmentioning
confidence: 99%
“…However, these values represent both the time for an exchange of sample solutions in the flow cell and the true response of the reactand in the layer. Gas-phase measurements with sensor layers using a CMOS-based calorimetric transduction of the chemical reaction have shown that the reaction of ETHT 4001 with dry !-butylamine in plasticised PVC can be as fast as 3 s for forward and 15 s for reverse response [15].…”
Section: Trifluoroacetylazobenzene Dyesmentioning
confidence: 99%
“…Reactands may overcome this limitation and may be used for the development of more selective and sensitive calorimetric and capacitive microsensors, because chemical reactions can provide changes in reaction enthalpy as well as in dipole moment. [41] Chemically reactive functional groups may also be introduced into conjugated polymers. The resulting materials might be used for the investigation of intra and intermolecular energy transfer (due to a change in the electron acceptor strength of the functional groups via chemical reactions) as well as for the preparation of supramolecular conjugates with chemically complementary macromolecules.…”
mentioning
confidence: 99%